Structural study of the oxidation process and stability of NbOxNy coatings - Chappé, J. M. (2008)
In the present work, we study the oxidation behaviour of NbON multilayer films. The films were deposited by DC magnetron sputtering with a reactive gas pulsing process. The nitrogen flow was kept constant and the oxygen flow was pulsed. Pulse durations of 10 s produced multilayered coatings with a period of k = 10 nm. Three different films with increasing duty cycles have been deposited. Rutherford backscattering spectroscopy (RBS) was used to study the chemical composition variations at different annealing temperatures (as-deposited, 400 C, 500 C and 600 C) combined with X-ray diffraction (XRD) to identify the crystalline phases formed. At 400 C, for all films a very thin layer starts to form at the surface with enhanced O concentration. The composition of the deeper part of the samples remains unchanged. At 500 C, the oxide scale grows, encompassing about half the film thickness. At 600 C, the process is finished and a single layer is formed with reduced Nb and increased O concentration. Fourier-transformation infrared spectroscopy (FTIR) results confirmed the increase of this surface oxidation, while XRD revealed that crystallization of Nb2O5 occurs at 600 C.